Elementary school wellness education an integrated approach to teaching the whole child - Cummiskey, Matthew 1974-; Cleland, Frances E. (Champaign, IL Human Kinetics, 2023)
"This book introduces school wellness education (SWE), which combines physical activity and health-enhancing skills into the same lesson. This enables students to receive a more holistic education across multiple domains of wellness. SWE meets multiple learning standards simultaneously and better uses limited class time"--
The School Wellness Approach -- The Whole School, Whole Community, Whole Child Model -- School Wellness Education: Emergent Pedagogies -- Online School Wellness Education -- Grades K-2 Lesson Plans -- Grades 3-5 Lesson Plans.
Includes bibliographical references (pages 213-218) and index.
Keywords: Health Education; School Health Services; Health Promotion; Physical Education and Training